"Continuing the Connection" or "Carrying On"? A Qualitative Evidence Synthesis of How Widows Explain the Physical Health Outcomes After Spousal Loss. (January 2022) - Majid, Umair; Ennis, Jeffrey
The experience of losing a loved one can have profound effects on physical and psychological well-being, and previous research has reported an increased risk of mortality after spousal loss. This qualitative evidence synthesis reviewed 16 studies on the perspectives of widows who experienced adverse physical health outcomes after spousal loss. This review examines how widows described or explained the physical health outcomes after losing their spouse. We found that widows implicitly associated the physical health outcomes they experienced with losing their spouse. They described that losing their spouse exacerbated preexisting illness and led to new disease conditions such as heart failure, rheumatoid arthritis, infections, acute urinary retention, shingles, and impaired mobility. While these physical health outcomes limited widows' ability to come to terms with their loss, widows in multiple studies prioritized the emotional and mental consequences associated with grief over any physical health outcomes they experienced. Furthermore, since the deceased spouse performed caregiving responsibilities, the surviving spouse experienced a shift from caregiving to self-management of their preexisting medical condition. In situations where widows were unable to meet their own health needs, they experienced an intensification of their own illness. Given these findings, we consider the relationship between widows' meaning-making and physical and clinical outcomes. We discuss how meaning-making can contribute to severe emotional, mental, and physical health outcomes after a traumatic event such as spousal loss.